Verification of EC Model's Effect to Forecast Precipitation in Beipan River Basin - KONG Xiangbo; XIA Xiaoling; CU Yuanke; TANG Yanjing; SONG Wanli; LIAO Bo (Renmin Zhujiang)
In order to test the precipitation forecast of the European central numerical model (hereinafter referred to as EC model) in the Beipan River Basin,this paper tests the forecast effect of different starting times and the overall forecast effect of 2020 flood season for an extreme precipitation process in the Beipan River Basin.The results are as follows:①For the prediction of 500 hPa circulation field,rainfall area,correlation coefficient between EC rainfall prediction and actual rainfall,and TS score of rainstorm,the shortened the prediction time is,the better the prediction effect will be.The effect is the most obvious for the maximum rainfall forecast adjustment,and the rainfall after adjustment is closer to the actual rainfall.The EC model is also applicable to forecast heavy rain.②In 2020,the forecast effect of no rain,light rain and moderate rain is better than that of heavy rain and rainstorm.EC model is almost not available to forecast severe rainstorm.③The rainstorm forecast effect differs with different basins,and the rainstorm forecast effect of Dongqing Basin is better than that of other basins.Therefore,it can be concluded that the correlation coefficient of EC model in the whole Beipan River Basin is about 0.9,and the ratio of the standard deviation of prediction to that of observation is 0.77,which indicates that EC model has good prediction effect for the trend of precipitation change,but there are some deviations in the area and magnitude.So,the forecast results can be applied after being corrected.